Síntese de compósitos adsorventes a base de quitosana para a remoção de corante alimentício e surfactante em meio aquoso - Mello, Jonatan Rafael de (2020)
The presence of substances, known as emerging contaminants, in industrial, agricultural and domestic effluents increase the search for applications of technologies other than traditional ones for water treatment. Thus, adsorption appears as an option for the removal of these compounds in the treatment of effluents. Chitosan has recognized application for the adsorption of various compounds in water. However, the chitosan powder "in natura", presents some disadvantages, such as the lack of exposure of its adsorption sites. This disadvantage can be minimized from the use of some techniques, such as sol-gel, which has stood out in the processes of material synthesis, because it allows the production of materials with structural advantages, high purity and homogeneity. Thus, the objective of this work is to develop an adsorbent with chitosan and silica from the sol-gel technique, and to verify if this composite is efficient in the removal of Tartrazine Yellow (AT) and Alkylbenzene Linear Sulfonates (LAS) surfactant by the adsorption technique. The relationship between the amount of chitosan and silica in the composite was evaluated on the adsorption properties of the material produced. The materials were characterized by FTIR, SEM, pHzpc and TG. The influence of pH, equilibrium concentration, time and temperature were evaluated on the adsorption of the substances. In addition, the life cycle of the material was evaluated with tests of regeneration and reuse of the composite in the adsorption of the AT dye. Finally, multicomponent adsorption was studied in order to verify the influence of the presence of LAS surfactant on AT dye adsorption. The 30%Chi adsorbent composite (with approximately 30% chitosan) was more efficient than the other materials in removing the dye. At pH of the 2.5 solution, the adsorption capacity of 144 mg/g and 136.57 mg/g for the AT dye and LAS was observed, respectively. Thermodynamic parameters identified that the adsorption is endothermic, spontaneous and favorable for the removal of the two substances. Weber and Morris' model showed that adsorption is controlled both by diffusion on the external surface and by diffusion inside the particle. In this context, it was observed that the chitosan adsorption capacity was increased by 60% due to the reduction of the steric impediment of its adsorption sites. The multicomponent adsorption showed that with the adsorption of the dye is influenced by the presence of LAS, reducing the adsorption capacity as the concentration of LAS was increased. The adsorption capacity of the LAS was not affected by the presence of the dye. Thus, it was concluded that the silica/chitosan based adsorbent composite has a high potential for the adsorption of the food colorant Tartrazine Yellow and the surfactant LAS.